Advanced Footwear Technology in Non-Elite Runners: A Survey of Training Practices and Reported Outcomes - Matteo Bonato; Federica Marmondi; Emanuela Luisa Faelli; Chiara Pedrinelli; Luigi Ferraris; Luca Filipas (Sports)
Background: Advanced footwear technology (AFT) has gained popularity among non-elite runners due to its potential benefits in training and competition. This study investigated the training practices and reported outcomes in non-elite runners using AFT. Methods: A cross-sectional observational study was conducted with 61 non-elite runners competing in distances ranging from 5 km to marathons. The survey collected data on demographics, training parameters, footwear usage, perceived changes in running mechanics, and self-reported injuries. Results: The results revealed a significant positive correlation (R = 0.6, p < 0.0001) between years of AFT use and weekly training volume, indicating that more experienced runners are likely to incorporate AFT consistently into their routines. Conversely, a significant negative correlation (R = −0.5, p < 0.0001) was found between training volume and the number of weekly sessions using AFT, suggesting a selective approach to footwear use. Participants reported biomechanical changes, such as increased forefoot support (49%) and higher calf muscle activation (44%), alongside a 16% self-reported injury rate, predominantly affecting the calves. Conclusions: These findings highlight the importance of proper guidance and gradual adaptation to maximize the benefits of AFT while minimizing injury risks. Future research should explore the long-term impact of AFT on performance and injury prevention through longitudinal studies.